ChemInform Abstract: The Effect of Benzyl Amine on the Efficiency of the Base‐Catalyzed Transamination of α‐Keto Esters. Issue 1 (3rd January 2013) - Xue, Fazhen; Xiao, Xiao; Wang, Haining; Shi, Yian
Abstract Transamination of α‐keto esters efficiently proceeds in the presence of a benzyl amine and triethylamine as catalyst.